(untitled) (Research, Society and Development, 2021)
Objective: The present study aims to analyze how ADHD interferes in the development and learning of children in the classroom, based on a literature review, findings related to the learning of children who have the disorder and how much they are in fact able to assimilate. contents, in teaching-learning processes. Methodology: This is an integrative literature review study, in which searches were performed in the LILACS database and the virtual library SCIELO. The combination of descriptors, based on the Health Sciences Descriptors - DeCS, used for the search were "Attention deficit hyperactivity disorder", "child", "schoolchildren", "teachers" and "teachers", used in the search the Boolean operators AND and OR. A time frame from 1996 to 2020 was used in the searches. 646 papers were found, but only 44 met the inclusion criteria for full analysis, resulting in 7 to compose the review. Two categories were directed to the discussion: the learning of children with ADHD and the teachers’ perception of the disorder. Conclusion: In general, studies show that children with the disorder have learning difficulties and low school performance. This disorder undeniably interferes significantly in the teaching-learning process of children in the school phase, making it a barrier to good academic performance.